On the Use of Compensatory Strategies in Simultaneous Interpretation - Al-Khanji, Raja; El-Shiyab, Said; Hussein, Riyadh (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractWeller (1990) believes that Krashen's concept of "comprehensible input" can play a key role in the simultaneous interpretation process even though this concept is most frequently cited in relation to second and foreign language learning. The "comprehensible input" concept is referred to here as the spoken or written pieces of information that are understood and interpreted by the hearer. Such information comes in the form of words, sentences, utterances, or even paragraphs.Based on Weller's recommendation, Krashen's concept is used as a framework for this study to analyze compensatory strategies employed by a small group of Jordanian interpreters who worked for an American television network during the Gulf War.This paper first examines the type of input that causes problems for interpreters.Second, it examines the strategies these interpreters use to compensate for difficult or incomprehensible input. The findings of the study detected five types of compensatory strategies that were employed by four interpreters. These strategies were grouped into two general types: achievement and reduction. These are discussed with recommendations at the end in the hope of providing more insight into how human beings process language under conditions of stress.